El uso de organizadores gráficos para mejorar la comprensión conceptual de los estudiantes - Flores Herrera, Jorge Rosendo (2018)
The purpose of this study was to construct a Word map using the Cmap® to improve conceptual understanding of students who are studying the course of Introduction to Didactics of the Mathematics and Physics at a public Ecuadorian University. The participants were 34 students, 19 men and 15 women, aged between 19 and 20 years. The instructional unit was "The constituent elements of the didactics of mathematics and physics". The time devoted to teaching was six hours. The instruments were the pretest and the posttests. The test was to write an essay of 300 words using a list of terms associated with the unit under study. The grades of the essay included the number of words, the ideas expressed and the use of the terms given in the list. The procedure followed in this study was as follows: (1) Administer the pretest, which lasted one hour. (2) Ask the students to build a Word map using the Cmap® program. This was done before class and worked individually. (3) Explain the content using the instructional strategy of R. Gagné, which lasted for six hours. (4) Administer the posttest. The statistical test was the paired t test with a significant level of p < 0,05. The use of the Words map improves the conceptual understanding of students.